2022
DOI: 10.3390/ijerph19031814
|View full text |Cite
|
Sign up to set email alerts
|

Learning to Cycle: From Training Wheels to Balance Bike

Abstract: Background: Learning to cycle is an important milestone in a child’s life, so it is important to allow them to explore cycling as soon as possible. The use of a bicycle with training wheels (BTW) for learning to cycling is an old approach practiced worldwide. Most recently, a new approach using the balance bike (BB) has received increased attention, and several entities believe that this could be most efficient. Drawing on the work of Bronfenbrenner (1995) and Newel (1986), this study aimed to analyse the effe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 32 publications
(42 reference statements)
0
10
0
Order By: Relevance
“…At the higher speeds, gliding becomes prevalent, leading the children to experience balance for longer periods, a skill which is necessary to ride a traditional bicycle. The previous literature supports the hypothesis that the BB is a better tool to learn to cycle independently when it is compared to the bicycle with lateral training wheels (BTW) because it seems to enable balance acquisition at the early stages of learning [ 13 , 14 , 16 , 17 ]. However, until now, it was not known which cycle patterns were more frequently explored by the children on a BB, nor what the preferred velocities were for the transition between them.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…At the higher speeds, gliding becomes prevalent, leading the children to experience balance for longer periods, a skill which is necessary to ride a traditional bicycle. The previous literature supports the hypothesis that the BB is a better tool to learn to cycle independently when it is compared to the bicycle with lateral training wheels (BTW) because it seems to enable balance acquisition at the early stages of learning [ 13 , 14 , 16 , 17 ]. However, until now, it was not known which cycle patterns were more frequently explored by the children on a BB, nor what the preferred velocities were for the transition between them.…”
Section: Discussionmentioning
confidence: 83%
“…In more recent times, a notable change has been the introduction of the balance bike (BB). A BB is a bicycle without pedals or training wheels, which is opposed to the previously standardized use of training wheels (stabilizers) on a regular bicycle [ 13 ]. The studies have indicated that the BB is a more effective learning tool than a traditional bicycle with lateral wheels is [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…After entering the new millennium, our findings reveal another drop in the age that children learn how to cycle independently. Possibly, this is due not only to the more central place the bike adopts within the family context nowadays, but also due to the transition from learning how to cycle with training wheels to the use of the balance bikes ( 55 , 60 ). In many countries, cycling is considered a traditional leisure time activity during childhood as many parents offer bikes to their children for playing when they are young.…”
Section: Discussionmentioning
confidence: 99%
“…This trend can be attributed to the increasing availability of dedicated cycling tracks and child-size-friendly bicycles, which make it easier for children to learn at an earlier age. However, many individuals who struggle to cycle independently as adults often trace their difficulties back to ineffective learning approaches [ 3 ]. Negative learning experiences, such as falling while learning to ride a two-wheel bike, can discourage them from persisting in their learning journey.…”
Section: Introductionmentioning
confidence: 99%